2013
DOI: 10.1002/jbmr.1917
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 Channels Protect Osteocytes Against Oxidative Stress–Induced Cell Death

Abstract: The increased osteocyte death by oxidative stress (OS) during aging is a major cause contributing to the impairment of bone quality and bone loss. However, the underlying molecular mechanism is largely unknown. Here, we showed that H2O2 induced cell death of primary osteocytes and osteocytic MLO-Y4 cells, and also caused dose-dependent decrease expression of gap junction and hemichannel-forming connexin 43 (Cx43). The decrease of Cx43 expression was also demonstrated with the treatment of other oxidants, roten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 39 publications
8
85
0
Order By: Relevance
“…Similar to the current report, immunohistochemistry studies showed that Cx43 expression in osteocytes decreases in old mice (Kar et al ., 2013). On the other hand, the expression of Cx43 is not decreased in osteoblastic cells isolated from old rats (Genetos et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the current report, immunohistochemistry studies showed that Cx43 expression in osteocytes decreases in old mice (Kar et al ., 2013). On the other hand, the expression of Cx43 is not decreased in osteoblastic cells isolated from old rats (Genetos et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased osteocyte apoptosis, mice lacking osteocytic Cx43 (Cx43 ΔOt ) exhibit enhanced endocortical resorption, partially mimicking the phenotype of old mice (Almeida et al ., 2007b) and raising the possibility that decreased Cx43 contributes at least in part to the skeletal phenotype of aging. However, while it has been shown that Cx43 levels in osteocytes are decreased in old mice (Kar et al ., 2013), the signaling pathway activated by Cx43 deficiency involved in osteocyte apoptosis with aging is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown relations to superoxide and oxidative stress 79 . Six genes with known links to oxidative stress and NO, within these 38 loci were identified (REST 48 , GJA1 49 , YAP1 50 , PRDM16 51 , LRP1 52 , and MRVI1 53 ). This is in line with previous findings 16 , however, in the DEPICT pathway analysis we found that NO-related reconstituted gene sets were not significantly associated with migraine (FDR > 0.54) (Supplementary Table 15).…”
Section: Discussionmentioning
confidence: 99%
“…Six of the loci harbor genes that are involved in nitric oxide signaling and oxidative stress (REST 48 , GJA1 49 , YAP1 50 , PRDM16 51 , LRP1 52 , and MRVI1 53 ).…”
Section: Supplementary Table 6)mentioning
confidence: 99%
“…Hemichannels are formed by 6 Cx proteins. Cx43 is the major connexin isoform expressed in bone cells and the activity of hemichannels induced by OS is primarily mediated by Cx43 hemichannels (8). Cx43 hemichannels have been shown to regulate the release of NAD + , prostaglandin E2 (PGE2), and ATP in response to mechanical stimulation in osteocytes (8).…”
Section: Introductionmentioning
confidence: 99%